Linguistic Homonyms and Synonymous Forms in the Qur’an and Their Influence on Qur’anic Meanings - Safi, Mahboob ur Rahman; Waiz, Abdul Aziz (Penerbit Hellow Pustaka, 2025)
This article examines an important linguistic topic closely tied to the understanding of the Qur’an: the phenomenon known as al-wujūh wa al naẓāʾir, or linguistic homonyms and their various semantic counterparts, and how they shape Qur’anic meanings. The importance of this study lies in the sensitivity of the topic especially for those involved in interpreting the Qur’an or translating its meanings since legal rulings and interpretive nuances often depend on such linguistic distinctions. To reach its conclusions, the researchers employed both inductive and applied methods They reviewed the major classical works that discuss wujūh and naẓāʾir, highlighted several examples, and applied this analysis to a specific Qur’anic term: “ḍaraba” (ضَرَبَ). The article ends with key findings and recommendations, one of which is that the study of wujūh and naẓāʾir is essential for students of Sharia and Arabic particularly mosque imams who are responsible for explaining the Qur’an This field is also a testament to the linguistic miracle of the Qur’an and reveals its profound eloquence The authors recommend that universities include this subject in their academic programs so that students can benefit from in.